2002
DOI: 10.1042/bj20011814
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of two cytidine deaminases in the nematode Caenorhabditis elegans

Abstract: Two cytidine deaminases (CDDs) from the free-living nematode Caenorhabditis elegans have been cloned and characterized. Both Ce-CDD-1 and Ce-CDD-2 are authentic deaminases and both exhibit RNA-binding activity towards AU-rich templates. In order to study their temporal and spatial expression patterns in the worm, reporter gene constructs were made using approx. 2kb of upstream sequence. Transfection of C. elegans revealed that both genes localized to the cells of the intestine, although their temporal expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…We found that dietary supplementation of uridine, thymidine, or cytidine, but not other nucleosides, fully restored the fertility of cdd-1/2 DKO worms ( Table 2). The rescue effect of uridine (product of CDD enzymes) or thymidine (derivative of uridine) (Lee et al 2009) is consistent with the previous finding that both CDD-1 and CDD-2 are authentic CDDs (Thompson et al 2002).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…We found that dietary supplementation of uridine, thymidine, or cytidine, but not other nucleosides, fully restored the fertility of cdd-1/2 DKO worms ( Table 2). The rescue effect of uridine (product of CDD enzymes) or thymidine (derivative of uridine) (Lee et al 2009) is consistent with the previous finding that both CDD-1 and CDD-2 are authentic CDDs (Thompson et al 2002).…”
Section: Resultssupporting
confidence: 79%
“…Our conclusion that CDD-1 and CDD-2 act on free nucleotides for the germline proliferation function is based on the following data: (1) A previous study determined that CDD-1/2 deaminate free nucleosides (Thompson et al 2002). (2) Our HPLC-UV measurements indicated a very low U/T:C ratio in the cdd-1/2 DKO worms (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins appear to be positioned evolutionarily between the cytidine and adenosine deaminase families, and deaminate an adenosine in the anticodon of certain yeast tRNAs (Gerber and Keller 1999). RNAi against each of the nine genes depicted in Figure 3 yielded no mutant phenotypes (Gönczy et al 2000;Kamath et al 2003), suggesting functional redundancy; embryonic defects may be associated with cdd-2(RNAi), however (Thompson et al 2002). Identification of the cytidine deaminase that edits gld-2 mRNA is now essential, but may be complicated by redundancy.…”
Section: Discussionmentioning
confidence: 99%
“…3), using the Superfamily program (Gough et al 2001). Two of the putative deaminases, CDD-1 and CDD-2, possess RNAbinding activity, and deaminate deoxycytidine in vitro (Thompson et al 2002). Another two candidate proteins, JC8.4 and Y47D3A.14, appear to be orthologs of budding FIGURE 1.…”
Section: Discussionmentioning
confidence: 99%